The efficacy and safety of Danggui-Sayuk-Ga-Osuyu-Saenggang-tang on Korean patients with cold hypersensitivity in the hands: study protocol for a pilot, double-blind, randomized, placebo-controlled, parallel-group clinical trial - Youme Ko (Trials, 2017)
Abstract Background In recent years, cold hypersensitivity in the hands (CHH) has become a common ailment of women in Korea. It can lead to gynecological problems such as irregular menstruation, miscarriage, and infertility. Traditionally, Korean herbal medicine has been the primary treatment method used to balance thermoregulation in the human body; however, its effectiveness has not been confirmed through systematic study. Thus, in this trial, we will investigate the feasibility of a full randomized clinical trial, Danggui-Sayuk-Ga-Osuyu-Saenggang-tang (DSGOST) in Korean women with CHH. Methods This study will be a pilot, multicenter, double-blind, randomized, parallel-group, two-arm, placebo-controlled clinical trial. A total of 66 participants will be randomly divided into two groups, a DSGOST treatment group and a placebo control group, in a 1:1 ratio using a web-based randomization system. Each group will take DSGOST or placebo three times daily for 6 weeks. The primary outcome will be measured using Visual Analogue Scale (VAS) scores of CHH. Secondary outcomes will include changes in skin temperature of the hands, Clinical Global Impressions (CGI) scale scores, recovery rate of skin temperature of the hands after the cold stress test, and the Korean version of the WHO Quality of Life Scale, abbreviated version (WHOQOL-BREF). Discussion This trial will be the first trial to reflect the newly defined disease range of CHH which was compiled by Korean medicine expert consensus. This study will provide considerable evidence for further large-scale trials and general clinical guidelines for CHH in the Korean medical field. Trial registration This study is registered at ClinicalTrials.gov, ID: NCT02645916 . Registered on 30 December 2015.